24 h movement behavior and metabolic syndrome study protocol: A prospective cohort study on lifestyle and risk of developing metabolic syndrome in undergraduate students from low-income regions during a pandemic - Nascimento-Ferreira, Marcus Vinicius; Marin, Kliver Antonio; Abrão Ferreira, Ruhena Kelber; Oliveira, Luiz Fernando; Bandeira, Ana Caroline; Silva Sousa, Paula; Miranda de Sousa, Josilene; de Almeida Cardoso, Antonio Gibran; Conceição da Silva, Lorrane Cristine; Rosa, Ana Clara Arrais; de Carvalho, Millena Vaz; Pereira de Carvalho Silva, Ithamara Sthefanny; et al. (Frontiers in Epidemiology, 2022)
Introduction: Obesity and its comorbidities are increasingly prevalent in Latin America, with a more rapid growth in individuals with lower income. The composition of movement behaviors within a 24-hour period may have important implications for obesity, metabolic and mental health in cross-sectional data. However, a longitudinal study is needed to confirm the findings from the primarily cross-sectional evidence. The Coronavirus disease 2019 (COVID-19) pandemic has been associated with cardiometabolic outcomes and has impeded healthy behaviour. Objectives: The first objective is to evaluate the time elapsed since the diagnosis of not meeting 24-hour movement guidelines and the potential subsequent onset of metabolic syndrome in undergraduate students from low-income regions within four years of follow up. The second objective is to test the association between 24-hour movement, mental wellbeing, eating behaviors, and abdominal obesity in the period of this pandemic. Methods: The 24-hour movement behaviour and metabolic syndrome (24h-MESYN) study is a multicentre cohort study that will include participants from two Brazilian cities within the 2022–2025 period to asses the first objective, and also a nested case-control study at the baseline will be carried out to evaluate the second objective. Previously, we conducted a feasibility study in the academic year of 2021 to assessing the psychometric properties of subjective tools, refine our study protocol, and adjust the epidemiological conditions of the cohort’s subsequent phases (like as prevalence of exposure of interest, sampling process and study adherence). Statistical tests as Cohen’s kappa agreement; factorial analysis; logistic, Poisson and linear regression; and Kaplan-Meier analysis will be performed, in accordance with the objectives.